Taxing the gender gap: Labor market effects of a payroll tax cut for women in Italy - Enrico Rubolino (W.E. Upjohn Institute for Employment Research, 2023)
This paper studies the labor market effects of a large payroll tax cut for female hires in Italy. Starting in January 2013, the payroll tax rate paid by the employer for female hires was reduced by 50 percent for a period of 12 months for temporary jobs and 18 months for permanent jobs. Eligibility for the tax cut depends on the time elapsed in nonemployment status and varies discontinuously by the worker's municipality of residence, age, and occupation. Combining social security data on the universe of Italian private-sector workers with several empirical approaches, I find that the tax cut increases female employment and spurs business performance, especially where gender biases are more severe. By contrast, the tax cut does not raise workers' net wages. A cost-benefit analysis implies that the net cost of the policy is around one-fourth of the budgetary cost. These findings provide the first empirical evidence that differentiating payroll taxes by gender helps to reduce the gender employment gap, but not the gender pay gap.
Keywords: H22; J21; J31; 330; gender gaps; female employment; payroll tax; tax incidence